Retrieval practice enhances new learning: the forward effect of testing - Pastötter, Bernhard; Bäuml, Karl-Heinz T. (Frontiers in Psychology, 2014)
In the last couple of years, there has been a dramatic increase in laboratory research examining the benefits of recall testing on long-term learning and retention. This work was largely on the backward effect of testing, which shows that retrieval practice on previously studied information, compared to restudy of the same material, renders the information more likely to be remembered in the future. Going beyond this prominent work, more recent laboratory research provided evidence that there is also a forward effect of testing, which shows that recall testing of previously studied information can enhance learning of subsequently presented new information. Here, we provide a review of research on this forward effect of testing. The review shows that the effect is a well replicated phenomenon in laboratory studies that has been observed for both veridical information and misinformation. In particular, the review demonstrates that the effect may be applied to educational and clinical settings, enhancing learning in students and reducing memory deficits in clinical populations. The review discusses current theoretical explanations of the forward effect of testing and provides suggestions for future research directions.